UMPSA establishes collaboration with D-8 International University, Iran, enhancing international cooperation - Mohd Ferdaus, Musa (UMPSA, 2023)
IRAN, 9 October 2023 - A formal working visit by a higher education delegation, led by the Vice-Chancellor of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Professor Dato’ Ts. Dr. Yuserrie Zainuddin, to the Islamic Republic of Iran recently witnessed the signing of a Memorandum of Understanding (MoU) between UMPSA and D-8 International University.